Determinants of intimate partner controlling behavior targeting women in Türkiye - Başkan, Burak; Alkan, Ömer (Frontiers in Psychology, 2023)
Background/aim Intimate partner controlling behavior toward women is an important form of intimate partner violence (IPV), both in terms of limiting women’s daily lives and in terms of reproducing patriarchal culture and male dominance in societies at the micro level. A limited number of studies in the literature have identified the male intimate partner’s controlling behavior as a dependent variable, which is important for understanding the determinants of this type of IPV. There is also a significant gap in the literature in terms of studies focusing on the case of Türkiye. Thus, the main aim of this study was to determine the socio-demographic, economic and violence-related factors that have an effect on women’s status in terms of exposure to control behavior in Türkiye. Methods These factors were examined by using binary logistic regression analysis, based on the micro data set collected by the Hacettepe University’s Institute of Population Studies in the 2014-dated National Research on Domestic Violence against Women in Türkiye. A total of 7,462 women between the ages of 15 and 59 were interviewed face-to-face. Results The findings of the study revealed that women are more likely to be exposed to controlling behavior if they live in rural areas, are unmarried, speak Turkish as their mother tongue, have bad or very bad health conditions, justify men’s violence and are afraid of their intimate partners. As women’s age, level of education and income contribution increase, their likelihood of exposure to controlling behavior decreases. However, women’s exposure to economic, physical and emotional violence also increases their likelihood of exposure to controlling behavior. Conclusion The findings highlighted the importance of creating public policies that make women less vulnerable to men’s controlling behavior, providing women with methods and mechanisms of resistance and raising public awareness of the exacerbating effects of controlling behavior on social inequalities.